Arthur Hugh Clough : the critical heritage - Thorpe, Michael (Critical heritage series., 1995)
The Critical Heritage gathers together a large body of critical sources on major figures in literature. Each volume presents contemporary responses to a writer's work, enabling students and researchers to read the material themselves.